Instrumento de gestão ambiental nos municípios do semiárido do estado de Alagoas - Marques Júnior, Eles Calheiros (2019)
The concern for the preservation of the environment gained strength in the world and Brazilian scenario especially from the decade of 1960, being included in the discussion agenda of the Academy, the business world, organized civil society and the Public Power. In Brazil, with the advent of the National Environmental Policy (PNMA), instituted by Law No. 6.938, dated August 31, 1981, and the Federal Constitution of 1988, the defense and preservation of the environment became competence and attribution of the Public Power at Federal, State and Municipal levels. In relation to the latter, it is necessary to analyze whether municipalities have the capacity to conduct efficient, effective and effective local environmental management. Thus, the general objective of this work is to evaluate if the municipalities of the Semi-arid of the State of Alagoas have installed capacity for environmental management, through the verification of the availability of environmental public policy instruments. The specific objective is to classify municipalities according to the availability of environmental management instruments and to elaborate the spatial representation of this classification. In order to meet the stated objectives, an exploratorydescriptive study was carried out, with a quantitative approach, through documentary analysis and statistical data provided by the Brazilian Institute of Geography and Statistics (IBGE). As a result, it was found that 68.42% of the municipalities of the Semi-arid of the State of Alagoas presented a critical or low level in relation to the availability of instruments for local environmental management. The unavailability of instruments makes it difficult to manage the environment, thus incapacitating the public authority of the municipalities of the Alagoas Semi-arid to adequately manage the local natural resources in response to the demands of the citizens and the environmental legislation in force in Brazil.